Capturing LiDAR‐Derived Hydrologic Spatial Parameters to Evaluate Playa Wetlands1. (8th October 2013) - Tang, Zhenghong; Li, Ruopu; Li, Xu; Jiang, Weiguo; Hirsh, Aaron
Abstract The digital elevation model data from traditional stereo photogrammetric methods are inadequate in providing accurate vertical parameters to feed hydrologic models for low‐lying, extremely flat areas. High‐resolution light detection and ranging (LiDAR) data provide the robust capability of capturing small variations in low‐relief playa wetlands. The Rainwater Basin in south‐central Nebraska includes a complex of seasonally shallow playa wetlands that attract millions of migratory waterfowl every spring and fall. This research focuses on the development of a procedure with applicable protocols to produce LiDAR‐derived three‐dimensional wetland maps and to extract the critical surface parameters (i.e., watershed boundaries, flow direction, flow accumulation, and drainage lines) for playa wetlands. The topo‐hydrologic conditions of playa wetlands were evaluated at the watershed level. The results show that in the Rainwater Basin, 70.7% of the historic hydric soil footprints identified in the Soil Survey Geographic (SSURGO) database were not functioning as topographically depressional wetlands. This finding was confirmed by a recent five‐year Annual Habit Survey showing that 69.8% of the historic hydric soil footprints did not function during the spring migratory bird seasons between 2004 and 2009. The majority of playa wetlands' topographic conditions have been substantially changed and the SSURGO data cannot fully reflect current topographic reality in the Rainwater Basin.